2021
DOI: 10.2147/cmar.s290966
|View full text |Cite|
|
Sign up to set email alerts
|

Matrine Regulates Proliferation, Apoptosis, Cell Cycle, Migration, and Invasion of Non-Small Cell Lung Cancer Cells Through the circFUT8/miR-944/YES1 Axis

Abstract: Background: Non-small cell lung carcinoma (NSCLC) is the major histological subtype of cancer cases. In the present study, we investigated the association between Matrine, an active component of Chinese medicine, and circFUT8 in NSCLC cells. Methods: The proliferation ability of NSCLC cells was assessed by MTT and colonyforming assays. Flow cytometry assay was performed to show the apoptosis and cell cycle distribution in NSCLC cells. The protein expression levels of Bcl-2, Cleaved Caspase-3 (C-Caspase3), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
(35 reference statements)
0
15
0
Order By: Relevance
“…Furtherly analysis suggested that the downregulation of miR-1298-5p could partly abolish the repression role of circ_0003028 knockdown on NSCLC progression. Additionally, circ_0003028 was reported to partake in the regulation of cell growth and metastasis in liver cancer and NSCLC by sponging multiple miRNAs [ 13 , 32 ]. These results inducted that circ_0003028 involves in complex regulatory networks.…”
Section: Discussionmentioning
confidence: 99%
“…Furtherly analysis suggested that the downregulation of miR-1298-5p could partly abolish the repression role of circ_0003028 knockdown on NSCLC progression. Additionally, circ_0003028 was reported to partake in the regulation of cell growth and metastasis in liver cancer and NSCLC by sponging multiple miRNAs [ 13 , 32 ]. These results inducted that circ_0003028 involves in complex regulatory networks.…”
Section: Discussionmentioning
confidence: 99%
“…Hsa-miR-186 was described downregulated in NSCLC, acting as an inhibitor of cancer proliferation, progression, and metastasis [40,41], whereas hsa-miR-1305 was not described in any type of cancer thus far. Another mechanism of action of circFUT8 in NSCLC has been described by Zhu et al [42] in a recent publication, where this circRNA was shown to increase proliferation, invasion, and migration of NSCLC cells via miR-944/YESI axis.…”
Section: Discussionmentioning
confidence: 83%
“…Another mechanism of action of circFUT8 in NSCLC has been described by Zhu et al. [ 42 ] in a recent publication, where this circRNA was shown to increase proliferation, invasion, and migration of NSCLC cells via miR‐944/YESI axis.…”
Section: Discussionmentioning
confidence: 90%
“…YES1 adjusts cell growth, survival, apoptosis, cell–cell adhesion, and cytoskeleton remodeling. Its levels have been found to be enhanced in patients with lung cancer, making it a potential therapeutic target in lung cancer [ 167 ]. The vital role of YES1 in lung carcinogenesis was revealed by its obstruction using the CRISPR/Cas9 system, leading to disrupted growth and metastasis of NSCLC by downregulation of mTOR signaling, a positive regulator of carcinogenesis [ 168 ].…”
Section: Crispr/cas9 In Cancersmentioning
confidence: 99%